Enteroaggregative Escherichia coli: Frequent, yet underdiagnosed pathotype among E. coli O111 strains isolated from children with gastrointestinal disorders in the Czech Republic - Klára Schlosserová; Ondřej Daniel; Klára Labská; Vladislav Jakubů; Tereza Stárková; Jan Bílý; Jiří Dresler; Christina Lang; Angelika Fruth; Antje Flieger; Helena Žemličková; Martina Bielaszewska; et al. (Elsevier, 2024)
Enteroaggregative Escherichia coli (EAEC) strains including those of serogroup O111 are important causes of diarrhea in children. In the Czech Republic, no information is available on the etiological role of EAEC in pediatric diarrhea due to the lack of their targeted surveillance. To fill this gap, we determined the proportion of EAEC among E. coli O111 isolates from children with gastrointestinal disorders ≤ 2 years of age submitted to the National Reference Laboratory for E. coli and Shigella during 2013-2022. EAEC accounted for 177 of 384 (46.1 %) E. coli O111 isolates, being the second most frequent E. coli O111 pathotype. Most of them (75.7 %) were typical EAEC that carried aggR, usually with aaiC and aatA marker genes; the remaining 24.3 % were atypical EAEC that lacked aggR but carried aaiC and/or aatA. Whole genome sequencing of 11 typical and two atypical EAEC O111 strains demonstrated differences in serotypes, sequence types (ST), virulence gene profiles, and the core genomes between these two groups. Typical EAEC O111:H21/ST40 strains resembled by their virulence profiles including the presence of the aggregative adherence fimbriae V (AAF/V)-encoding cluster to such strains from other countries and clustered with them in the core genome multilocus sequence typing (cgMLST). Atypical EAEC O111:H12/ST10 strains lacked virulence genes of typical EAEC and differed from them in cgMLST. All tested EAEC O111 strains displayed stacked-brick aggregative adherence to human intestinal epithelial cells. The AAF/V-encoding cluster was located on a plasmid of 95,749 bp or 93,286 bp (pAAO111) which also carried aggR, aap, aar, sepA, and aat cluster. EAEC O111 strains were resistant to antibiotics, in particular to aminopenicillins and cephalosporins; 88.3 % produced AmpC β-lactamase, and 4.1 % extended spectrum β-lactamase. We conclude that EAEC are frequent among E. coli O111 strains isolated from children with gastrointestinal disorders in the Czech Republic. To reliably assess the etiological role of EAEC in pediatric diarrhea, a serotype-independent, PCR-based pathotype surveillance system needs to be implemented in the future.